2019
DOI: 10.3390/agronomy9030144
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of the High Silicate and Phosphate Solubilizing Novel Strain Enterobacter ludwigii GAK2 that Promotes Growth in Rice Plants

Abstract: Silicon (Si) and phosphorus (P) are beneficial nutrient elements for plant growth. These elements are widely used in chemical fertilizers despite their abundance in the earth’s crust. Excessive use of chemical fertilizers is a threat to sustainable agriculture. Here, we screened different Si and P solubilizing bacterial strains from the diverse rice fields of Daegu, Korea. The strain with high Si and P solubilizing ability was selected and identified as Enterobacter ludwigii GAK2 through 16S rRNA gene sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 38 publications
4
62
0
1
Order By: Relevance
“…Sharing of P solubilization mechanism with Si also restrict the identification of microbes with Si solubilization property. Comparison of the designed medium with other reported silicon media (Sheng et al, 2008;Kang et al, 2017;Vasanthi et al, 2018;Lee et al, 2019) showed that NBRISSM has the best reproducibility in terms of Si solubilization and least P interference. Designing of such specific medium for screening of silicon-solubilizing microbes would be salutary and an option of using the second most available element of earth's crust in agriculture through green technologies for sustainable development.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Sharing of P solubilization mechanism with Si also restrict the identification of microbes with Si solubilization property. Comparison of the designed medium with other reported silicon media (Sheng et al, 2008;Kang et al, 2017;Vasanthi et al, 2018;Lee et al, 2019) showed that NBRISSM has the best reproducibility in terms of Si solubilization and least P interference. Designing of such specific medium for screening of silicon-solubilizing microbes would be salutary and an option of using the second most available element of earth's crust in agriculture through green technologies for sustainable development.…”
Section: Discussionmentioning
confidence: 92%
“…Most of aforementioned media for screening of Sisolubilizing microbes are either based on the plate assays for their zone formation ability (Kang et al, 2017;Lee et al, 2019) or liquid media containing soluble P sources like K 2 HPO 4 and Na 2 HPO 4 (Sheng et al, 2008;Vasanthi et al, 2018). There are no prior reports about the preparation of defined medium for high throughput screening (qualitative, indicator dye based) of silicon-solubilizing bacteria with discrimination of P solubilization.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations